(3GHSJehGhLjG Ydhe GdEYdGe h GdEJUGd (B/s - (3GdfPjQ, YHO Gddg GdKGfj eMeOs ((3GdLRGFQ(B;(3GdLRGFQ (B:s (3OGQ GdGOjH ,s, 2017)
(3GHSJjehdhLjG Ydhe GdEYdGe h GdEJUGd cCdjI dfbO GdaYd GdEYdGej h GdEJUGdj JHbi QgjfI JWhQ GdhSjdI Gh GdhSjW Ydi MO JYHjQ GdeacQ GdEYdGej GdcfOj eGQTGd eGcdhgGf h eGJaQRg gPg GdJcfhdhLjGJ ef SdhcGJ LOjOI JDKQ Ydi GdeeGQSGJ GdEJUGdjI Ch HGdCMQi GdaYd GdEJUGdj aGdELJgGOGJ GdEHSJehdhLjG aj gPG GdejOGf QGLYI dadSaI JWhQ JGQjN hSGFd GdEJUGd aj fSb JcfhdhLjs
Keywords: (3GHSJehdhLjGs; (3GdEHSJehdhLjGs; (3GdEYdGe GdMQs; (3Ydhe GdEYdGe h GdEJUGds